Novel Urinary Biomarkers and Chronic Kidney Disease After Coronary Angiography: A Prospective Case-Controlled Study - Soliman, Amin Roshdy; Yosry, Ahmed; Samir, Hussein H.; Abdelaziz, Tarek; Soliman, Haytham; Ahmed, Rabab Mahmoud (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Novel urinary biomarkers may have potential for early detection of acute kidney injury. AIM: The aim of the study was to test two urinary biomarkers: Kidney injury molecule-1(KIM-1) and liver-type fatty acid binding protein (L-FABP) as markers of kidney injury following coronary angiography. METHODS: This is a prospective non-randomized controlled trial, performed in two large teaching hospitals. Patients were recruited from the catheter lab or form nephrology outpatient clinics. In group (A), 100 patients with AKI on top of CKD after coronary angiography and Group B: Thirty-one patients with stable CKD as a control. KIM-1 and L-FABP were measured at base line and after 3 months. RESULTS: In group (A), 100 patients who had acute on top of CKD after coronary angiography, stage progression occurred in 15 patients in group (A) compared to two patients in group (B) (p = 0.28). The median change in eGFR after 3 months was not statistically significant between both groups (p = 0.8). Median baseline urinary liver-type fatty acid binding protein was higher in Group A compared to Group B (3.7 μg/g vs. 1.82μg/g). The change in L-FABP from baseline to 3 months was significant between both groups (p < 0.001). The median urinary concentrations of KIM-1 and L-FABP were higher at the end of the follow-up compared to base line values in both groups, (p < 0.000). CONCLUSION: Urinary L-FABP correlates with kidney function decline in patients with acute on top of CKD after coronary angiography. Urinary levels of KIM-1 and L-FABP at 3 months increase significantly compared to baseline in patients with progressive CKD.